Synthesis Of Silicon-Based Nanostructures By Chemical Vapour Growth On Silicon Wafer And From Pyrolysis Of Oil Palm Fibres - Chiew , Yi Ling (2012)
Silicon-based nanostructures were successfully synthesized from two different routes of chemical vapour growth (CVG) on silicon wafers and pyrolysis of oil palm fibres. In CVG, SiC nanorods, SiC nanocolumns as well as SiC/SiO2 core-shell nanowires, nanocables and nanowebs were produced by heating only Si wafers and activated carbon powder (ACP) under vacuum/argon at 1300°C. The oxidation time, soaking time and amount of ACP influenced the morphologies of nanostructures. SiC nanorods and nanocolumns were formed at soaking time of 1 hour, with increasing diameter and yield when oxidation time was raised from 1 to 12 minutes.